(untitled) (Journal of Nuclear Technology in Applied Science, 2020)
Diagnostic x-radiation is an essential part of present-day medical practice being the largest contributor of irradiation to the general population. Therefore, routine checking of x-ray tubes leakage is very important to ensure that leakage radiation at a one-meter distance from focus is less than 1mR/h. The measurement of background radiation was performed during normal departmental working hours: early in the morning before the machines were switched on, and after the machines were switched on. Exposures were performed using different exposure factors and the fall out radiation in both control and uncontrolled areas were also recorded. The highest equivalent dose rate was recorded in the uncontrolled area of room 2, where the mean dose rate was 26.21 μSv/h (in changing room) and 11.67 μSv/h (behind the door), respectively. It follows the dose rate measured in the uncontrolled area of room 1, where the mean dose rate was 6.33 μSv/h (behind the door), 2.96 μSv/h (in changing room B), and 1.56 μSv/h (in changing room A), respectively. The lowest radiation dose was measured in both controlled and uncontrolled areas of CT-scan, where the mean dose rate was 0.17 μSv/h and 0.16 μSv/h, respectively, simply because the room doors and wall are adequately lead-lined and protected. All values obtained in this study are within the permissible limit, except that for uncontrolled areas in x-ray rooms 1 and 2, where radiation dose rates were higher than the reference limit for public exposure.